2019
DOI: 10.3389/fnagi.2019.00168
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Kinin B2 Receptor in Organotypic Hippocampal Cultures of Middle-Aged Mice

Abstract: Aging is a multifactorial phenomenon that results in several changes at cellular and molecular levels and is considered the main risk factor for some neurodegenerative diseases. Several evidence show the participation of the kallikrein-kinin system (KKS) in neurodegeneration and this system has been associated with inflammation and immunogenic responses in the central and peripheral systems by the activation of the B1 and B2 receptors. Previous work by our group showed that bradykinin (BK) and the B2 receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In order to evaluate the secreted substances associated with the activation of the BKB2R, we adopted the organotypic hippocampal culture (OHC) model using a reduced number of animals (four per group/treatment). Our laboratory has developed a method that allows the maintenance of healthy hippocampal slices of adult animals (12 months old) for a long period of time [ 12 ]. To confirm the viability and good maintenance of the hippocampal slices from the WT and TG animals over the 28 days in vitro (28DIV), we stained the slices with propidium iodide to quantify cell death.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to evaluate the secreted substances associated with the activation of the BKB2R, we adopted the organotypic hippocampal culture (OHC) model using a reduced number of animals (four per group/treatment). Our laboratory has developed a method that allows the maintenance of healthy hippocampal slices of adult animals (12 months old) for a long period of time [ 12 ]. To confirm the viability and good maintenance of the hippocampal slices from the WT and TG animals over the 28 days in vitro (28DIV), we stained the slices with propidium iodide to quantify cell death.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of the BKB1R cannot be discarded; Sanden et al demonstrated that BKB1R is upregulated after lipopolysaccharide (LPS) injection, resulting in an increase in TNFα and IFNɣ [ 33 ]. Another study recently published by our group demonstrated the importance of animals’ age with respect to the neuroprotective action of bradykinin and BKB2R [ 12 ]. In this study, a decrease in inflammatory markers was observed after treatment with BK only in 12-month-old animals; in 6-month-old animals, kinin receptor activation increased inflammatory markers [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations